Analisis Banjir Akibat Sudetan Meandering Sungai Kolokoso Studi Kasus : Bandara Dhoho, Kediri - M Gilang Indra Mardika; Tera Melya Patrice Sihombing; Ryan Andreas (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
The construction of Dhoho Kediri Airport has altered land use in the Kolokoso Watershed, increasing flood risks. To mitigate this, a cutoff channel was proposed for the meandering river section. Hydrological analysis utilized the Log Pearson III distribution and Mononobe method for a 25-year return period. Effective rainfall was derived via the Alternating Block Method, and peak flood discharge was calculated at 0.829 m³/s using the SCS Unit Hydrograph. HECRAS 6.4.1 simulations modeled the implementation of three box culverts (4.8 m x 4.3 m). Results indicate a significant reduction in flood inundation area from 5.93 ha to 0.65 ha. Validation demonstrated high model accuracy, showing 89% agreement for water levels and98% for flow velocities.